A generic competency framework for entry level construction managers in Malaysia / Haryanti Mohd Affandi - Mohd Affandi, Haryanti (2014)
The changes in industry needs have further highlighted the problems of incompetence entry level construction managers and brought significant changes in construction management education. Moreover, culmination from the issues faced in the entry level construction management, it suggests that there is problem relating to the mismatch of generic competency in entry level construction management. The mismatch of generic competency appears when there are changes in industry requirements added with education provision in developing construction management students’ generic competency. Furthermore, there’s an absence of strategic framework for Malaysian entry level construction managers. The aim of this research is to address part of the problem in construction management generic competency education and construction industry by suggesting an improved generic competency framework of entry level construction managers in Malaysia. This study adopts a mixed method approaches and results from questionnaire survey and interviews which highlight the major issues. Sequential explanatory model are chosen in determining the mismatch. In developing the generic competency framework, this study adapts and improves Spencer & Spencer (1993) competency development model. Responses for questionnaire surveys were collected from contactors and undergraduate construction management students and have been analyzed by inferential statistical analyses using Winsteps. Qualitative analysis was done by validating the framework and explaining the existence of mismatch. Results from this study, manage to develop a generic competency framework for entry level construction managers based on their roles and tasks. This framework consists of 12 generic competencies which are communication, behavioral characteristics, negotiation, teamwork, leadership, problem solving, entrepreneurship, ethics, analytical and critical thinking, flexibility, lifelong learning and relationship building. From this framework, this study determines the mismatch between industry requirement and construction management students expectation towards generic competency. This study find the existence of mismatch are contributed by students attitude, inexperience lecturers and less opportunity in experienced onsite work during internship. The results in general reveal that students attitude play significant roles in the existence of mismatch. Moreover, from the finding, it is suggested that industry and university need to improve their collaboration in exchanging knowledge and experience in enhance the construction management students generic competency.